(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the concepts of social morality and etiquette through the hadiths presented in Imam al-Bukhari’s work Al-Adab al-Mufrad. The book frequently addresses concepts related to social responsibilities, including respect for parents, neighborly relations, compassion, justice, kindness, and social upbringing. The study applies a literary-analytical method (textual study of the book), examining the hadith texts and their social meanings. The article shows the role of Al-Adab al-Mufrad in shaping social harmony, moral communication among people, and the culture of etiquette. The conclusion provides the significance of the work for modern society and practical recommendations.